Influence of Peripheral Artery Disease and Statin Therapy on Apolipoprotein Profiles - Andrew W. Gardner; Petar Alaupovic; Donald E. Parker; Polly S. Montgomery; Omar L. Esponda; Ana I. Casanegra (International Journal of Vascular Medicine)
Apolipoprotein B is a stronger predictor of myocardial infarction than LDL cholesterol, and it is inversely related to physical activity and modifiable with exercise training. As such, apolipoprotein measures may be of particular relevance for subjects with PAD and claudication. We compared plasma apolipoprotein profiles in 29 subjects with peripheral artery disease (PAD) and intermittent claudication and in 39 control subjects. Furthermore, we compared the plasma apolipoprotein profiles of subjects with PAD either treated (n=17) or untreated (n=12) with statin medications. For the apolipoprotein subparticle analyses, subjects with PAD had higher age-adjusted Lp-B:C (P<0.05) and lower values of Lp-A-I:A-II (P<0.05) than controls. The PAD group taking statins had lower age-adjusted values for apoB (P<0.05), Lp-A-II:B:C:D:E (P<0.05), Lp-B:E + Lp-B:C:E (P<0.05), Lp-B:C (P<0.05), and Lp-A-I (P<0.05) than the untreated PAD group. Subjects with PAD have impaired apolipoprotein profiles than controls, characterized by Lp-B:C and Lp-A-I:A-II. Furthermore, subjects with PAD on statin medications have a more favorable risk profile, particularly noted in multiple apolipoprotein subparticles. The efficacy of statin therapy to improve cardiovascular risk appears more evident in the apolipoprotein sub-particle profile than in the more traditional lipid profile of subjects with PAD and claudication. This trial is registered with ClinicalTrials.gov NCT00618670.